2020
DOI: 10.1002/cpt.1811
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Cruciferous Vegetable‐Enriched Diets on Drug Metabolism: A Systematic Review and Meta‐Analysis of Dietary Intervention Trials in Humans

Abstract: Relatively few studies exist in the literature that discuss the effects of diet on drug metabolism and how this can affect interindividual differences in systemic drug exposure. Several studies have investigated the effects of cruciferous vegetables (Cruciferae) or their constituents on drug‐metabolizing activity, as these vegetables form an important part of many peoples’ diets. In general, the ingestion of cruciferous vegetables is associated with induction of cytochrome P450 (CYP) 1A2 activity in vivo; howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…Hypokalemia is reported (Baretta et al 2009 ; Guo and Mei 2016 ). Due to the laxative effect, a changed absorption of orally applied anticancer medication is also conceivable Unlikely: Plasma levels probably too low to achieve relevant potential inhibition of CYP2D6 or CYP3A4 (Djuv and Nilsen 2012 ) Angocin Nasturtium and horseradish root Unlikely Beetroot See: Calcium, vitamin C Possible: Reduction in effects of anthracyclines and other regimes by antioxidative action of betanin (Nestora et al 2016 ) Brazil nuts Unlikely Broccoli Likely: Reduction in effects of cisplatin by GST-α induction (Allocati et al 2018 ; Eagles et al 2020 ) Possible: Reduction in effects of other regimes through GST modulation and e.g., resulting conferring of resistance to chemotherapy (Allocati et al 2018 ) Possible: Reduction in effects of anthracyclines and other regimes by antioxidative action of sulphoraphane (Ferreira et al 2018 ; Zeller et al 2013 ) Chinese herbs mixtures Likely: Cytochrome (CYP) interactions (Zeller et al 2013 ) depending on the different ingredients Likely: Interactions with endocrine therapy by phytoestrogens (Zeller et al 2013 ) Possible: Other interactions (Zeller et al 2013 ) depending on the different ingredients Curcuma longa Possible: Interactions by multiple cytochrome (CYP) effects and an inhibition of Pgp (Al-Jenoobi et al 2015 ; Cho and Yoon 2015 ; Volak et al 2008 ) Possible: Interactions with immunotherapy by multiple effects on the immune system and immunosuppressive action (Fahey et al 2007 ; Kang et al 1999 ; Skyvalidas et al 2020 ) Possible: Reduced chemotherapy-induced apoptosis in cancer cells for camptothecin, cyclophosphamide, doxorubicin, mechlorethamine (Somasundaram et al 2002 ), and other regimes by antioxidative effects * * Due to the broad spectrum of interactions, especially due to antioxidative action, interactions with other chemotherapeutic agents than with the regimes investigated so far also seem possible Garlic …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hypokalemia is reported (Baretta et al 2009 ; Guo and Mei 2016 ). Due to the laxative effect, a changed absorption of orally applied anticancer medication is also conceivable Unlikely: Plasma levels probably too low to achieve relevant potential inhibition of CYP2D6 or CYP3A4 (Djuv and Nilsen 2012 ) Angocin Nasturtium and horseradish root Unlikely Beetroot See: Calcium, vitamin C Possible: Reduction in effects of anthracyclines and other regimes by antioxidative action of betanin (Nestora et al 2016 ) Brazil nuts Unlikely Broccoli Likely: Reduction in effects of cisplatin by GST-α induction (Allocati et al 2018 ; Eagles et al 2020 ) Possible: Reduction in effects of other regimes through GST modulation and e.g., resulting conferring of resistance to chemotherapy (Allocati et al 2018 ) Possible: Reduction in effects of anthracyclines and other regimes by antioxidative action of sulphoraphane (Ferreira et al 2018 ; Zeller et al 2013 ) Chinese herbs mixtures Likely: Cytochrome (CYP) interactions (Zeller et al 2013 ) depending on the different ingredients Likely: Interactions with endocrine therapy by phytoestrogens (Zeller et al 2013 ) Possible: Other interactions (Zeller et al 2013 ) depending on the different ingredients Curcuma longa Possible: Interactions by multiple cytochrome (CYP) effects and an inhibition of Pgp (Al-Jenoobi et al 2015 ; Cho and Yoon 2015 ; Volak et al 2008 ) Possible: Interactions with immunotherapy by multiple effects on the immune system and immunosuppressive action (Fahey et al 2007 ; Kang et al 1999 ; Skyvalidas et al 2020 ) Possible: Reduced chemotherapy-induced apoptosis in cancer cells for camptothecin, cyclophosphamide, doxorubicin, mechlorethamine (Somasundaram et al 2002 ), and other regimes by antioxidative effects * * Due to the broad spectrum of interactions, especially due to antioxidative action, interactions with other chemotherapeutic agents than with the regimes investigated so far also seem possible Garlic …”
Section: Resultsmentioning
confidence: 99%
“…Likely: Reduction in effects of cisplatin by GST-α induction (Allocati et al 2018 ; Eagles et al 2020 )…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that the consumption of large amounts of cruciferous vegetables, such as broccoli, Brussels sprouts, cabbage, cauliflower, and radishes, can induce CYP1A2 and glutathione S-transferase-alpha (GST-α) in humans, 30 which may have chemopreventive effects against chemical or toxic compound-induced cell damage and carcinogenesis. However, the effects of SPL consumption on hepatic detoxification systems have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The targeted clozapine plasma level was 350 ng/mL (55). If the clozapine plasma level was under 350 ng/mL, we systematically searched for all possible causes of low clozapine plasma level such as poor compliance, inflammatory syndrome, tobacco or caffeine consumption, drug (phenytoin, carbamazepine, and rifampicin), and food (char-grilled meat and cruciferous vegetables such as cabbage, Brussels sprouts, turnips, spinach, or broccoli), all known for their possible interaction leading to enzyme induction (55)(56)(57)(58)(59). After eliminating these causes, we performed pharmacogenetics testing for CYP.…”
Section: Introductionmentioning
confidence: 99%